2003
DOI: 10.1542/peds.111.4.860
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Autoimmune, and HLA Characteristics of Children Diagnosed With Type 1 Diabetes Before 5 Years of Age

Abstract: Children diagnosed with type 1 diabetes before 5 years of age may have different diabetes-related autoimmune and genetic characteristics from those diagnosed at a later age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
54
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 18 publications
12
54
2
2
Order By: Relevance
“…That came in agreement with the results of Hathout et al [3] who reported-that neonates, infants and toddlers with type 1 diabetes are more likely to have a father with type 1 diabetes than diabetic children diagnosed at a later age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…That came in agreement with the results of Hathout et al [3] who reported-that neonates, infants and toddlers with type 1 diabetes are more likely to have a father with type 1 diabetes than diabetic children diagnosed at a later age.…”
Section: Discussionsupporting
confidence: 93%
“…This came in agreement with the work of Hathout et al [3] showed a higher frequency of diabetic ketoacidosis in the early onset group at the time of presentation. Joseph et al [22] reported that even in developed countries, 15-70% of all newly diagnosed infants and children with diabetes present with DKA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Whereas many studies have relied on clinical findings alone to distinguish between type 1 diabetes and type 2 diabetes, examining autoimmune measures in these youth reveals interesting findings. Hathout et al (54) reported that 30.3% of subjects with a clinical diagnosis of type 2 diabetes had positive GAD65Abs and 34.8% had positive IAAs, out of 48 youth followed in that center with clinical type 2 diabetes. DAAs and T-cell reactivity were compared in children and adolescents who presented with findings of type 1 diabetes, type 2 diabetes, or an admixture of clinical findings.…”
Section: Diabetes Classification and Daasmentioning
confidence: 99%
“…differences in the frequencies of HLA alleles and haplotypes from other T1D age groups. None of the 40 patients with EOD analyzed in a study by Hathout et al 52 Since completion of the HapMap project and the development of massively parallel array-based genotyping technologies, the results of genome-wide association studies (GWASs) have uncovered dozens of additional solidly replicated loci. [53][54][55][56][57][58] Several consortia analyzed a remarkable number of individuals within cohorts of cases and controls (with trios in 1 study), using .200 000 markers for GWASs.…”
Section: Figurementioning
confidence: 99%